Poor outcome despite modern treatments: A retrospective study of 99 patients with primary and secondary plasma cell leukemia - Camille Tessier; Richard LeBlanc; Jean Roy; Sabrina Trudel; Julie Côté; Marc Lalancette; Jean‐Samuel Boudreault; Émilie Lemieux‐Blanchard; Rayan Kaedbey; Michel Pavic (Cancer Medicine)
Abstract Background Plasma cell leukemia (PCL) is a rare monoclonal gammopathy, associated with short survival. Because of its very low incidence, only a few cohorts have been reported and thus, information on this disease is scarce. The goal of this study was to better understand the clinical features, prognostic factors, and efficacy of modern treatments in both primary PCL (pPCL) and secondary PCL (sPCL). Methods We performed a retrospective, multicenter study of patients diagnosed with PCL, defined as circulating plasma cells ≥20% of total leukocytes and/or ≥2 × 109/L. Results We identified 99 eligible PCL patients, of whom 33 were pPCL and 66 were sPCL. The median progression‐free survival (PFS) to frontline treatment and overall survival (OS) were, respectively, 4.8 (95% CI, 0.4–9.2) and 18.3 months (95% CI, 0.0–39.0) for pPCL and 0.8 (95% CI, 0.5–1.1) and 1.2 months (95% CI, 0.9–1.5) for sPCL (both p < 0.001). We observed no improvement in OS over time (2005–2012 vs. 2013–2020, p = 0.629 for pPCL and p = 0.329 for sPCL). Finally, our data suggested that sPCL originates from a high‐risk multiple myeloma (MM) population with a short OS (median 30.2 months), early relapse after stem cell transplant (median 11.9 months) and a high proportion of patients with multiple cytogenetic abnormalities (36% with ≥2 abnormalities). Conclusions This study is one of the largest PCL cohorts reported. We are also the first to investigate characteristics of MM before its transformation into sPCL and demonstrate that high‐risk biologic features already present at the time of MM diagnosis. Moreover, our data highlights the lack of improvement in PCL survival in recent years and the urgent need for better treatment options.